2005
DOI: 10.1007/s00445-005-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Long term exposure to respirable volcanic ash on Montserrat: a time series simulation

Abstract: Frequent ash fallout from long-lived eruptions (with active phases greater than 5 years) may lead to local populations experiencing unacceptably high cumulative exposures to respirable particulate matter. Ash from Montserrat has been shown to contain significant levels of cristobalite and other reactive agents that are associated with an increased risk of developing pneumoconiosis (including silicosis) and other long-term health problems. There are a number of difficulties associated with estimating risks in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…fresh deposits of Mount St. Helens in the US (Hobbs et al, 1983), Soufriere Hills in Montserrat (Hincks et al, 2006), Mount Hudson in the southern Argentinean Patagonia , Eyjafjallajökull in Iceland (Thorsteinsson et al, 2012;Leadbetter et al, 2012), and Cordón Caulle in the central Argentinean Patagonia, which is addressed in this paper.…”
Section: Folch Et Al: Modeling Volcanic Ash Resuspensionmentioning
confidence: 98%
“…fresh deposits of Mount St. Helens in the US (Hobbs et al, 1983), Soufriere Hills in Montserrat (Hincks et al, 2006), Mount Hudson in the southern Argentinean Patagonia , Eyjafjallajökull in Iceland (Thorsteinsson et al, 2012;Leadbetter et al, 2012), and Cordón Caulle in the central Argentinean Patagonia, which is addressed in this paper.…”
Section: Folch Et Al: Modeling Volcanic Ash Resuspensionmentioning
confidence: 98%
“…Studies by Hincks et al (2006) and Barsotti et al (2010) also linked the resuspension to the amount of tephra cover and showed the direct correlation between the thickness of tephra deposit to the higher concentrations of PM 10 and 10 µm volcanic particles, respectively.…”
Section: Tephra Fallout In Urban Settlementsmentioning
confidence: 99%
“…Damby et al, 2013;Hincks et al, 2006;Horwell et al, 2003Horwell et al, , 2007Le Blond et al, 2010;Searl et al, 2002;Wilson et al, 2011). The finer particles, especially particulate matter with dimensions ≤10 µm or PM 10 in aerodynamic equivalent diameter (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of tephra fallout on human populations range from acute and chronic health effects (Blong 1984;Sigurdsson et al 2000;Horwell and Baxter 2006;Hincks et al 2006) to pollution of water supply (Blong 1984;Stewart et al 2006) and disruption of the economy (Blong 1984). Precise studies after major eruptions have shown the complex and nonlinear response of these aspects to tephra fallout (Johnston et al 2000).…”
Section: Social Riskmentioning
confidence: 99%
“…Precise studies after major eruptions have shown the complex and nonlinear response of these aspects to tephra fallout (Johnston et al 2000). Therefore, uncertain and wide ranges of individual exposures, natural variation in individual response, change in eruptive behaviour with time and meteorological conditions at the time of the eruption increase the difficulty of producing risk assessment for social aspects (Hincks et al 2006). As an example, our social vulnerability maps are very simplified and only consider the aspects of (1) total population, (2) education level and (3) age classes, on which the effects of tephra fallout are mainly unclear and indirect.…”
Section: Social Riskmentioning
confidence: 99%